Bioengineered Factor IX Molecules with Increased Catalytic Activity Improve the Therapeutic Index of Gene Therapy Vectors for Hemophilia B - Brunetti-Pierri, Nicola (Mary Ann Liebert, Inc., 2009)
Although the desire to develop gene therapy for hemophilia B is high, safety remains a concern. Therefore, improving the therapeutic index of gene therapy vectors is an important goal. Thus, we evaluated the use of three bioengineered factor IX (FIX) variants with improved catalytic activity in the context of the helper-dependent adenoviral vector. The first vector expressed R338A-FIX, an FIX variant with the arginine at position 338 changed to an alanine, which resulted in a 2.9-fold higher specific activity (IU/mg) compared with the wild-type FIX. The second vector expressed FIX(VIIEGF1), a variant with the EGF-1 domain replaced with the EGF-1 domain from FVII, which resulted in a 3.4-fold increase in specific activity. The third expressed R338A + FIX(VIIEGF1), a novel variant containing both aforementioned modifications, which resulted in a 12.6-fold increase in specific activity. High-level, long-term, and stable expression of these three variants was observed in hemophilia B mice with no evidence of increased thrombogenicity compared with wild-type FIX. Thus, these bioengineered FIX variants can increase the therapeutic index of gene therapy vectors by permitting administration of lower doses to achieve the same therapeutic outcome. Furthermore, these variants may also be valuable for recombinant FIX protein replacement therapy.